(untitled) (Tabanque. Revista Pedagógica, 2020)
The article aims to reconstruct a path of political and philosophical hermeneutics concerning the pedagogical theme of the profile and the role of the teacher in the era of cyberculture and social knowledge. This issue is dealt with according to the indications of the tradition of social sciences and French post-structuralism. Starting from the definition of “General Intellect” in Marx, passing through “the immaterial” of Gorz, up to Lévy’s“collective intelligence”, we will analyze the proposal of conceptual trees as a tool for training and experimentation for the formation of individuals and communities by the specifications training agencies. A proposal for the benefit of a revival of the social role of the school.